The safety and immunogenicity of a two-dose schedule of CoronaVac, and the immune persistence of vaccination for six months, in people living with HIV: A multicenter prospective cohort study - Wang, Yuxiao; Qiao, Ying; Huo, Yuqi; Wang, Li; Liang, Shijie; Yu, Maohe; Lan, Xinquan; Song, Moxin; Zhang, Xiangjun; Yan, Ying; Xu, Junjie (Frontiers in Immunology, 2023)
Background People living with HIV (PLWH) are more vulnerable to SARS-CoV-2. However, evidence on the immunogenicity of coronavirus disease 2019 (COVID-19) vaccines in this population is insufficient. The objective of this study is to assess the immunogenicity and safety of the two-dose schedule of Sinovac CoronaVac for 6 months postvaccination in PLWH. Methods We conducted a multicenter prospective cohort study among PLWH and HIV-negative adults in China. Participants who received two doses of CoronaVac prior to the recruitment were allocated into two groups and followed up for 6 months. The neutralizing antibodies (nAbs), immunoglobulin G against the receptor-binding domain of the spike protein (S-IgG), and gamma-interferon (IFN-γ) were measured to assess the associations among CoronaVac immunogenicity and related factors. Adverse reactions were collected to evaluate the safety profile of vaccination. Results A total of 203 PLWH and 100 HIV-negative individuals were enrolled. A small portion of participants reported mild or moderate adverse reactions without serious adverse events. Median nAbs level in PLWH (31.96 IU/mL, IQR: 12.34-76.40) was lower than that in the control group (46.52 IU/mL, IQR: 29.08-77.30) at the 2-4 weeks postvaccination (P=0.002), and the same trend was presented for median S-IgG titer (37.09 vs. 60.02 IU/ml) (both P <0.05). The nAbs seroconversion rate in the PLWH group was also lower than in the control group (75.86% vs. 89.00%). After then, the immune responses reduced over time in term of only 23.04% of PLWH and 36.00% of HIV-negative individuals had a positive seroconversion for nAbs at 6-month. The multivariable generalized estimating equation analysis showed that PLWH with CD4+T count≥350 cells/µL presented higher immune response than PLWH with CD4+T count <350 cells/µL in terms of antibody seroconversion and titers. The immunogenicity did not differ in participants with low or high HIV viral load. The S-antigen specific IFN-γ immunity was generally stable and had a slow attenuation in both two groups for 6 months postvaccination. Conclusion The Sinovac CoronaVac was generally safe and immunogenic in PLWH, but the immunity response was inferior and the antibodies vanished faster compared to HIV-negative individuals. This study suggested a shorter than 6-month interval of prime-boost vaccination for PLWH to ensure a better protection.